2006
DOI: 10.1111/j.1472-8206.2006.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a surgical procedure to measure drug biliary excretion of rats in regulatory safety studies

Abstract: A surgical procedure was evaluated to allow bile collection from the freely moving male Sprague-Dawley rats for the assessment of drug biliary excretion during regulatory safety studies. A catheter was implanted into the bile duct to divert the bile flow via an exteriorized loop. Following recovery from the surgery and verification of normal hepatic function, the exteriorized catheter was sectioned to allow collection of the bile and replacement with a commercial bile salt solution. Approximately 80% of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…5,6 The loss of BW in groups A and B did not reach statistical significance at any time point and was regained 4 -5 days after surgery, which is consistent with BW loss previously reported in BDC rats. 6,11 Surgery has a debilitating effect 11,13 and weight loss was most likely due to surgery-related stress rather than the specific surgical procedure, as demonstrated by the similarity between groups A and B. This means that the simplification of the BDC method did not compromise the wellbeing of the animals more than a simple laparotomy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 The loss of BW in groups A and B did not reach statistical significance at any time point and was regained 4 -5 days after surgery, which is consistent with BW loss previously reported in BDC rats. 6,11 Surgery has a debilitating effect 11,13 and weight loss was most likely due to surgery-related stress rather than the specific surgical procedure, as demonstrated by the similarity between groups A and B. This means that the simplification of the BDC method did not compromise the wellbeing of the animals more than a simple laparotomy.…”
mentioning
confidence: 99%
“…18 Postoperative variations in clinical biochemistry parameters were described by van Wijk et al 11 who noted them to be outside normal limits in rats following surgery. Also, Faure et al 13 reported enzyme and total bilirubin parameters outside the normal range on day two in 15 -65% of rats following surgery, but approximately half of these animals regained normal values eight days postsurgery. Furthermore, deviations in liver enzymes have been reported by West et al 19 in BDC rabbits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The animal is then placed back to metabolic cage and externalized tubing is attached to a dual channel swivel. The bile flow needs to be closely monitored for 1-2 h before the studies [30], and if possible, liver function tests can be performed by monitoring the level of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and bilirubin [31]. Control bile is collected from the bile-duct cannula up to 0.5 h pre dose.…”
Section: Bilementioning
confidence: 99%
“…An extracorporeal BDC bypass loop is implanted into the rats by surgery (Lipsky and Berkley, 1977) to collect bile specimens from the animals under unrestrained freely moving conditions (Balabaud et al, 1981). However, the BDC surgery sometimes causes hyperbilirubinemia (HB) (Faure et al, 2006). Decreased hepatobiliary transport of bilirubin and its glucuronides is a possible cause of the HB in such rats.…”
Section: Introductionmentioning
confidence: 99%